Enormous changes at the last minute stories - Paley, Grace 1922-2007 (Farrar, Straus, Giroux, 1974)
Seventeen stories written over the past fifteen years reveal the author's vision of human love and tragedy.
Keywords: Geschichte 1900-2000; Alltag, Brauchtum; USA; United States -- Social life and customs -- 20th century -- Fiction; Anthologie